Staging Masculinity in Ancestral and Colonial Legacies in Sembene Ousmane’s Cinematic Debut during Senegal’s Independence Interlude (1960-1965) - Bayo, Saiba (COMUNICACIÓN. Revista Internacional de Comunicación Audiovisual, Publicidad y Estudios Culturales, 2023)
This article studies the genesis of Sembene Ousmane’s cinema during the early years of Senegal’s independence. Sembene was a renowned anti-colonial Senegalese writer who shifted to filmmaking during the "independence interlude" spanning 1960 to 1965, with his first film Borom Sarret (1963). He became a pioneer of African cinema. Sembene revolutionary filmmaking and radical artistic project catapulted him to the pantheon of worldwide filmmakers. Drawing from postcolonial film criticism, this article focuses on two of Sembene’s pioneering films: Borom Sarret and Niaye. I argue that Sembene strategically crafted these films to genuinely contribute to the collective effort of postcolonial reconstruction. I start with a brief review of Sembene’s literary works during the independence interlude to understand how this period influenced his artistic perspective and cinematic narrative regarding gender. I then dive into the analysis of masculinity and colonial legacy in Borom Sarret and finally focus on Niaye to study how Sembene depicts the collective memory and patriarchal dynamics in a pseudo-feudal society in transition from colonialism to independence, tradition to modernity. The article contributes to a better understanding of how Sembene approached social transformation, navigated (post)colonial power structures shaped by colonial and ancestral legacies, and established himself as an iconoclastic artist.